Assessment on Social Vulnerability and Response Towards Natural Disaster in A Disaster-Prone Coastal Village: An Example from Bangladesh - Kabir, Md. Humayain; Hossain, Tanvir (International Journal of Disaster Management, 2021)
Due to geographical locations, the Southwestern coastal region of Bangladesh is frequently experiencing climate change induced disasters such as cyclones, floods, and tidal surges. However, local communities at this region have a long history of coping with the adverse effects of these disasters. Consequently, this research assessed the social vulnerability towards natural disasters through local peoples perception and identified the existing immediate response against natural disasters at Kazirchar village in Muladi Upazila of Barishal district of the coastal region. In this study, a well-structured questionnaire survey, and focus group discussions were conducted to collect primary data. The collected data were processed and analysed to present the existing impacts of natural disasters. Besides, the immediate responses were categorized into different sectors. The study found that, the most prevalent coastal disaster in Kazirchar village was cyclone. About 48% of surveyed respondents opined that high cost of living was the main reason for increasing the vulnerability towards disasters. To adapt with disaster impacts, 58% respondents of this village need to travel long distances to collect drinking water. On the other hand, during flood, 26% people took shelter on government-owned high lands, whereas 40% shifted temporarily to their neighbors who are living in house with a high land elevation. This research concludes that the village has a low prior preparedness against various disasters, less knowledge about disaster, less coordination and poor collaboration between government organization (GOs) and non-governmental organizations (NGOs) regarding disaster risk reduction. It is expected that this study will act as a source of information for taking natural disaster management initiatives and the findings of this study will push the policy makers to develop and implement long term adaptation strategies in coastal areas of Bangladesh particularly in Barishal district.